Whitman, il montaggio e la nascita del Nuovo Mondo (PHILM. Rivista di filosofia e cinema, 2024)
This essay aims to discuss how the birth of a nation might be as a poetic montage process. The article presents the genesis of the American nation as a montage of different and disparate elements, drawing inspiration from some of the most evocative lyrics of American poet Walt Whitman. The argument put forth is that the nation’s political, social, and aesthetic complexity can be understood by embracing its multiplicity. In this sense, Dziga Vertov can be considered Whitman’s cinematic heir. Both believe that a new world can only be announced by a new montage in which the elements connect unpredictably and freely, yet leaving space for the interval between them, an interval from which the “outside” emerges.